2019
DOI: 10.3390/rs11010071
|View full text |Cite
|
Sign up to set email alerts
|

Group Line Energy in Phase-Resolved Ocean Surface Wave Orbital Velocity Reconstructions from X-band Doppler Radar Measurements of the Sea Surface

Abstract: The wavenumber-frequency spectra of many radar measurements of the sea surface contain a linear feature at frequencies lower than the first order dispersion relationship commonly referred to as the “group line”. Plant and Farquharson, showed numerically that the group line is at least partially caused by wave interference-induced breaking of steep short gravity waves. This paper uses two wave retrieval techniques, proper orthogonal decomposition (POD) and FFT-based dispersion curve filtering, to examine two X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Kammerer and Hackett [8] show that phase-resolved ocean wave fields are reconstructed from X-band Doppler radar measurements of the ocean surface by proper orthogonal decomposition (POD) more accurately than the conventional FFT-based dispersion curve filtering. The results indicate that the group line (a linear feature at frequencies lower than the first order dispersion relationship in wavenumber-frequency spectra of the ocean surface) influences the phase-resolved wave field.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Kammerer and Hackett [8] show that phase-resolved ocean wave fields are reconstructed from X-band Doppler radar measurements of the ocean surface by proper orthogonal decomposition (POD) more accurately than the conventional FFT-based dispersion curve filtering. The results indicate that the group line (a linear feature at frequencies lower than the first order dispersion relationship in wavenumber-frequency spectra of the ocean surface) influences the phase-resolved wave field.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Therefore, many studies focus on removing the nonlinear components from the wavenumberfrequency spectrum to improve the accuracy of ocean wave parameter inversion. Kammerer et al [19]- [21] demonstrated that retaining part of "Group-Line" energy in significant wave height inversion can improve inversion accuracy when "Group-Line" energy is greater or comparable to dispersion curve energy. Hwang et al [22] used a high-pass filter with a cutoff frequency of 0.04 Hz to filter out part of the "Group-Line" energy, but the wave period was overestimated.…”
Section: Introductionmentioning
confidence: 99%